Bank Credit During the 2008 Financial Crisis : A Cross-Country Comparison - Aisen, Ari (IMF Working Papers; Working Paper ;, 2010)
This paper empirically estimates the main determinants of bank credit growth during the 2008 financial crisis. Using a sample covering over 80 countries, this paper finds that larger bank credit booms prior to the crisis and lower GDP growth of trading partners are among the most important determinants of the post-crisis bank credit slowdown. Structural variables such as financial depth and integration were also relevant. Finally, countercyclical monetary policy and liquidity played a critical role in alleviating bank credit contraction after the 2008 financial crisis, suggesting that countries should pursue appropriate institutional and macroeconomic frameworks conducive to countercyclical monetary policies.